ANALISIS PENGUAT DAYA TERIMA ANTENA YAGI OMNIDIRECTIONAL TERHADAP PENGAMATAN SIARAN TELEVISI MENGGUNAKAN DUA PERBANDINGAN BOOSTER - ., SANDYONO SINAMBELA (Jurnal Teknik Elektro Universitas Tanjungpura, 2018)
Television antenna booster function as an amplifier of the loss (losses) signal received from the antenna through the coaxial cable that is too long, The incoming signal to the antenna through the cable RF signal is very weak. Booster itself works as an RF signal amplifier and also act as a selector which frequencies used by television receiver (VHF or UHF). Yagi antenna is a directional antenna that has a directional pattern radisi that can receive power in one direction. Using a booster antenna without causing reception less than the maximum for multiple stations within quite a distance from the receiving antenna. This study aimed to compare the two, namely television antenna booster SUNNYCO and TOYOSAKI using Omnidirectional Yagi antenna. SINPO ie code numbers to assess the strength of the signal, interference, noise from the atmosphere, propagation conditions, and the general impression of the reception. Assessment is done with numbers ranging from 5 (excellent) to 1 (very bad). Description result the picture quality of television antenna booster using SINPO approach as a reference of the quality of images produced. The quality of images produced by the booster SUNNYCO have a better quality than the quality of the images produced by the booster TOYOSAKI. Â Keywords:Â  Booster television antennas, Omnidirectional Yagi antennas, SINPO, SUNNYCO Booster, booster TOYOSAKI